The development of the adrenal gland in pig hybrids during the embryonic and postembryonic life (Morphological and Histometrical study). - ΤΗΝΙΑΚΟΣ, Γ.; ΣΑΜΠΑΤΑΚΟΣ, Ο.; ΣΤΟΦΟΡΟΣ, Ε. (Journal of the Hellenic Veterinary Medical Society, 2019)
1. The mean absolute weight of the pig adrenals, during the embryonic and postembryonic life, follows a continiously increasing curve which is parallel to the body weight. 2. On the contrary, the curves of the relative weight and of the relation between adrenals and kidneys weight follow the above curves only until birth. After birth they follow a continuously decreasing curve. So, in hybrids of 15.000-20.000 gr of body weight the adrenals weight is the same as in embryos of 117 gr. 3. The general development of the adrenal cortex is parallel to the absolute weight. 4. The development of the zona glomerulosa is slower in relation to the zona fasciculate especially during the postembryonic life. So, the relation of the zona glomerulosa and fasciculate in embryos of mean weight 40 gr, 117 gr, 261 gr, 442 gr, 640 gr, 2239 gr, 8500 gr, 13600 gr, and 22000 gr, was correspondingly 1/2, 1/4, 1/4, 1/4, 1/4, 1/10, 1/10, 1/10, 1/10. 5. We did not observe signs of involution or degeneration of cortex during the embryonic and postembryonic life.